2021
DOI: 10.1080/20002297.2021.1909917
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of a small molecule compound II-6s against oral streptococci

Abstract: Background:The side effects of present antimicrobials like chlorhexidine (CHX) and the emergence of drug resistance necessitate the development of alternative agents to control dental caries. Aim: This study developed a novel small molecule, namely II-6s, and investigated its antimicrobial activities against common oral streptococci associated with dental caries. Methods: The susceptibility of streptococci to II-6s was evaluated by the microdilution method, time-kill assay and scanning electron microscopy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Further modifications of NPS-2143 yield a compound II-6s ( Chen Y et al., 2019 ). Our group demonstrated that II-6s effectively inhibited the growth of S. mutans , reduced EPS production and induced no drug resistance in S. mutans after repeated treatment as compared to CHX, indicating its potential use in the control of dental caries ( Zhang J et al., 2021 ).…”
Section: Small Molecules That Inhibit Keystone Bacteria Associated Wi...mentioning
confidence: 93%
See 1 more Smart Citation
“…Further modifications of NPS-2143 yield a compound II-6s ( Chen Y et al., 2019 ). Our group demonstrated that II-6s effectively inhibited the growth of S. mutans , reduced EPS production and induced no drug resistance in S. mutans after repeated treatment as compared to CHX, indicating its potential use in the control of dental caries ( Zhang J et al., 2021 ).…”
Section: Small Molecules That Inhibit Keystone Bacteria Associated Wi...mentioning
confidence: 93%
“…MIC 90 : 3.91 mg/ml(Zhang J et al, 2021) MBC 90 : 15.63 mg/ml MBIC 90 : 3.91 mg/ml MBRC 90 : 62.5 mg/ml inhibit the demineralization of tooth enamel and induce no drug resistance in S…”
mentioning
confidence: 99%
“…It been confirmed that S. mutans can develop high levels of resistance to it [ 12 , 13 ]. Chlorhexidine, which is the gold standard for controlling dental plaque clinically, acts on bacterial cell walls and induces strain resistance in S. mutans [ 14 ]. The imperceptible low-frequency resistance of the drug may be due to its multiple different targets [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a simultaneous association with drug resistance and tolerance has been reported. For instance, reports suggest that chlorhexidine induces drug resistance in S. mutans, and the fungus Candida albicans may produce persisters after treatment with chlorhexidine [10,11]. In addition, the indiscriminate bactericidal effect of chlorhexidine would dramatically affect the microecology of oral microflora.…”
Section: Introductionmentioning
confidence: 99%